Efektivitas Ozonated Virgin Coconut Oil Dosis Bertingkat Terhadap Penyembuhan Luka Full Thickness Skin Graft Autolog Ditinjau Dari Jumlah Fibroblas Dan Ekspresi Vascular Endothelial Growth Factor Pada Tikus Sprague Dawley - Napitupulu, Johan Rinto Even; Hardian, Hardian; Najatullah, Najatullah (Medica Hospitalia : Journal of Clinical Medicine, 2021)
Abstract Background: Now, Skin grafts are one of the therapies of choice in the wound healing process. And this is still developing today. The process of formation fibroblas and the formation of vascular endothelial growth factor have an important role in healing skin graft wounds. Ozonated virgin coconut oil has an important role in wound healing. Objective: To prove the effect of ozonated virgin coconut oil in various doses in increasing number of fibroblas and expression of vascular endothelial growth factor of skin graft wounds. Methods: This study is an experimental study with "Randomized parallel study with controlled group design" on 40 Sprague Dawley rats which are performed an autologous skin graft at the same time. Samples were divided randomly into 8 groups (K1 and K2 = without ozonated VCO), (A1 and A2 = ozonated VCO 50,4 mg/ml), (B1 and B2 = ozonated VCO 103,2 mg/ml), (C1 and C2 = ozonated VCO 204 mg/ml). Evaluation of the amount of fibroblas was done by staining hematoxylin & eosin after the 6th day and the expression of vascular endothelial growth factor was done by staining immunohistochemistry after the 12th day after skin graft. Results: Statistical analysis of the amount of fibroblas after the 6th day was found to be significantly different between the K1 vs A1 group (p = 0.029), K1 vs B1 (p = 0.004), K1 vs C1 (p = 0.000), on the 12th day was found significantly different the amount of fibroblast between K2 vs A2 ( p = 0,029 ), K2 vs B2 ( p = 0,010 ), K2 vs C2 ( p = 0,001 ). The expression of vascular endothelial growth factor on the 6th day was found a significant difference between the K1 vs A1 group (p = 0.024), K1 vs B1 (p = 0.005), K1 vs C1 (p = 0.001), on the 12th day was found significantly different the expression of vascular endothelial growth factor between K2 vs A2 ( p = 0,011 ), K2 vs B2 ( p = 0,036 ), K2 vs C2 ( p = 0,004 ) . Conclusion: Ozonated VCO can increase the amount of fibroblas and expression of vascular endothelial growth factor in the wound healing process of autologous skin graft in Sprague Dawley rats. Keywords: Ozonated VCO, full thickness skin graft, fibroblas, VEGF.